2012
DOI: 10.1108/s0885-2111(2012)0000014007
|View full text |Cite
|
Sign up to set email alerts
|

When Online Recycling Enables Givers to Escape the Tensions of the Gift Economy

Abstract: International audienceThe present article explores a relatively new way for consumers to dispose of items they no longer use, namely free recycling websites. Online recycling is based on an encounter with an unknown recipient to give something away 'in person'. A phenomenological approach was used to understand the meaning of giving through free recycling websites. Placing the focus on the donor's perspective, we analysed Internet postings and conducted 27 in-depth interviews. Our research shows that (1) when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Enacted by participants in free reuse groups by Self-transcendence Reducing one's environmental impact by extending the lifespan of an item (Foden, 2012); Helping someone in need to obtain an item that could improve their quality of life (Groomes and Seyfang, 2012;Guillard and Bucchia, 2012b;Nelson and Rademacher, 2009); Supporting one's local community (Nelson et al, 2007).…”
Section: Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Enacted by participants in free reuse groups by Self-transcendence Reducing one's environmental impact by extending the lifespan of an item (Foden, 2012); Helping someone in need to obtain an item that could improve their quality of life (Groomes and Seyfang, 2012;Guillard and Bucchia, 2012b;Nelson and Rademacher, 2009); Supporting one's local community (Nelson et al, 2007).…”
Section: Valuementioning
confidence: 99%
“…Motivations for giving away items include seeking to: experience the pleasure associated with the act of making a gift (Nelson and Rademacher, 2009); avoid the inconveniences of other forms of waste disposal (Groomes and Seyfang, 2012;Guillard and Bucchia, 2012b); make a charitable gift to a person in need (Guillard and Bucchia, 2012b;Nelson and Rademacher, 2009); support the local community (Nelson et al, 2007); or, act on environment concerns (Foden, 2012). Motivations for requesting items include seeking to: save money by acquiring items for free (Nelson et al, 2007); act on environment concerns (Foden, 2012); acquire items to resell for profit or for charitable causes (Freecycle, 2009); or, through financial necessity, acquire items that could not otherwise be afforded (Foden, 2012).…”
Section: Self-direction Independent Thought and Action Stimulationmentioning
confidence: 99%
“…Research has shown that people use Internet platforms (for example, the French website www.recupe. net) in order to gain a sense of belonging in a community of donors (Nelson et al 2007) or to foster the possibility to choose and perhaps meet the future recipient of their objects, or to be recognized as donors (Guillard and Del Bucchia 2012). Others choose ''hybrid options'' (Scaraboto 2015) like selling to flea markets (where giving and selling are mixed) to meet the future beneficiary of the gift or to have the opportunity to meet people who share a passion for a particular object (Herrmann 1997;Garcia-Bardidia 2014).…”
Section: The Four Main Areas Of Marketing Research Where the Concept mentioning
confidence: 98%
“…Le Gall Ely and Urbain (2011) show how people escape from the ''straightjacket of social expectations'' (Marcoux 2009) by resorting to the market instead of asking for help from relatives, or by giving gifts to associations instead of relatives in order to avoid negative effects like dependence, humiliation, and oppression between giver and receiver. In order to escape these tensions, consumers may choose to give goods to ''strangers'' (Guillard and Del Bucchia 2012).…”
Section: The Four Main Areas Of Marketing Research Where the Concept mentioning
confidence: 99%
See 1 more Smart Citation